The Dark Side of Managing Human– AI Collaborations: Implications for Leaders’ Moral Relativism and Unethical Behaviour - He, Guohua; Ni, Dan; Zhao, Puchu; Qin, Xin (Journal of Management Studies, 2026)
Abstract As collaborations between humans and artificial intelligence (AI) have become increasingly prevalent across various industries, the role of leaders in managing these collaborations has grown in importance. While the existing literature has highlighted the benefits of leader management in these settings – emphasizing the complementary strengths of humans and AI – the potential costs to key stakeholders, particularly to leaders themselves, have been largely ignored. This research addresses this gap by drawing on moral relativism theory to develop and test a model explaining how leader management of human–AI collaborations may induce leaders’ moral relativism and, in turn, result in unethical behaviour at work. Furthermore, we identify leaders’ need for cognitive closure as a crucial individual difference that negatively moderates these effects. Findings from a critical‐incident experiment, two scenario‐based experiments, and one field survey conducted with samples from both Western and Eastern cultures (i.e., the United States and China) support our model.